Objective-C for Absolute Beginners iPhone, iPad and Mac Programming Made Easy - Bennett, Gary; Lees, Brad; Fisher, Mitchell (Apress : Imprint: Apress, 2016)
You have a great idea for an app, but how do you bring it to fruition? Objective-C is the universal language of iPhone, iPad, and Mac apps, and this book starts you on the path to mastering this language and its latest release, and also addresses how to mix Swift with Objective-C. Using a hands-on approach, you'll learn how to think in programming terms, how to use Objective-C to construct program logic, and how to synthesize it all into working apps. Gary Bennett, an experienced app developer and trainer, will guide you on your journey to becoming a successful app developer. If you're looking to take the first step towards App Store success, Objective-C for Absolute Beginners, Third edition is the place to start. Readers will be treated to the following and much more: The fundamentals of computer programming: how to understand variables, design data structures, and work with file systems The logic of object-oriented programming: how to use Classes, Objects, and Methods The flexibility of Apple's developer tools: how to install Xcode and write programs in Objective-C How to make OS X applications or iOS apps that do cool stuff.